Heading towards a better world. Part 1: wisdom, compassion, and personal responsibility. Issue 9 (20th October 2016) - Ernst, Richard R.
Abstract : This essay in two parts summarizes the author's view on the personal and institutional responsibility of researchers and universities for enabling a beneficial future of our globe. All too often, we have lost a greater perspective and are living shortsightedly on the account of the weaker members of today's society and depredate the resources of future generations. In this situation, academics and universities carry a heavy load of responsibility, remembering that they educate the citizens of tomorrow, especially their political, economic, and spiritual key leaders. – The first part addresses the educational aspects for enhancing comprehension of those essential aspects that determine the fate of mankind. – The second part starts with a brief analysis of some current trends and formulates the particular responsibility of universities resulting from it.